Incorporating SGLT2i and GLP-1RA for Cardiovascular and Kidney Disease Risk Reduction: Call for Action to the Cardiology Community. Issue 1 (7th July 2021) - Nelson, Adam J.; Pagidipati, Neha J.; Aroda, Vanita R.; Cavender, Matthew A.; Green, Jennifer B.; Lopes, Renato D.; Al-Khalidi, Hussein; Gaynor, Tanya; Kaltenbach, Lisa A.; Kirk, Julienne K.; Lingvay, Ildiko; Magwire, Melissa L.; et al.
Abstract : Multiple sodium glucose cotransporter-2 inhibitors (SGLT-2i) and glucagon-like peptide-1 receptor agonists (GLP-1RA) have been shown to impart significant cardiovascular and kidney benefits, but are underused in clinical practice. Both SGLT-2i and GLP-1RA were first studied as glucose-lowering drugs, which may have impeded uptake by cardiologists in the wake of proven cardiovascular efficacy. Their significant effect on cardiovascular and kidney outcomes, which are largely independent of glucose-lowering effects, must drive a broader use of these drugs. Cardiologists are 3 times more likely than endocrinologists to see patients with both type 2 diabetes and cardiovascular disease, thus they are ideally positioned to share responsibility for SGLT-2i and GLP-1RA treatment with primary care providers. In order to increase adoption, SGLT-2i and GLP-1RA must be reframed as primarily cardiovascular and kidney disease risk-reducing agents with a side effect of glucose-lowering. Coordinated and multifaceted interventions engaging clinicians, patients, payers, professional societies, and health systems must be implemented to incentivize the adoption of these medications as part of routine cardiovascular and kidney care. Greater use of SGLT-2i and GLP-1RA will improve outcomes for patients with type 2 diabetes at high risk for cardiovascular and kidney disease.